Specialization for support teachers. Assessing the educational innovation in a perspective of quality - Antonio Calvani; Laura Menichetti; Marta Pellegrini; Tamara Zappaterra (Firenze University Press, 2017)
The Ministry of Education in Italy has launched several initiatives to foster inclusive school system; the Specialization Course for Support Teacher (D.M. 30.09.2011) attests the institutional willingness to make this educational area an organic and unavoidable component of future teachers professionalism. In this paper we analyze the approach and outcomes of the first two cycles of the Specialization Course for Support Teacher held at the University of Florence in the years 2013-2014 and 2014-2015: they represented a test case to evaluate possibilities and problems in implementing an institutional innovation in a complex area as inclusion. We intend to provide indications for the construction of a model of quality and show how the Course will be exposed to a circular process of improvement to influence the third edition in 2017.   La formazione per il sostegno. Valutare l'innovazione didattica in un'ottica di qualità Il MIUR ha avviato diverse iniziative per favorire un sistema scolastico inclusivo; il Corso di Specializzazione per il Sostegno (D.M. 30.09.2011) attesta la volontà istituzionale di rendere questo ambito della formazione una componente organica e imprescindibile della professionalità dei futuri insegnanti. Nel presente contributo si analizzano l'impostazione e gli esiti dei primi due cicli del Corso di Specializzazione per il sostegno tenutisi presso l'Università di Firenze, negli anni 2013-2014 e 2014-2015: essi hanno rappresentato un banco di prova per valutare possibilità e criticità nell'attuare una innovazione istituzionale in un ambito complesso come quello dell'inclusione. Intendiamo quindi avanzare indicazioni per la costruzione di un modello di qualità e mostrare come il Corso possa essere sottoposto ad un processo circolare di miglioramento in grado di interessare anche la terza edizione del 2017.